Antiferroelectric PbSnO3 Epitaxial Thin Films. Issue 35 (26th October 2022) - Lai, Yu‐Hong; Zheng, Jun‐Ding; Lu, Si‐Cheng; Wang, Yin‐Kuo; Duan, Chun‐Gang; Yu, Pu; Zheng, Yun‐Zhe; Huang, Rong; Chang, Li; Chu, Ming‐Wen; Hsu, Ju‐Hung; Chu, Ying‐Hao
Abstract: In condensed matter physics, oxide materials show various intriguing physical properties. Therefore, many efforts are made in this field to develop functional oxides. Due to the excellent potential for tin‐based perovskite oxides, an expansion of new related functional compounds is crucial. This work uses a heteroepitaxial approach supported by theoretical calculation to stabilize PbSnO3 thin films with different orientations. The analyses of X‐ray diffraction and transmission electron microscopy unveil the structural information. A typical antiferroelectric feature with double hysteresis and butterfly loops is observed through electrical characterizations consistent with the theoretical prediction. The phase transition is monitored, and the transition temperatures are determined based on temperature‐dependent structural and electrical characterizations. Furthermore, the microscopic antiferroelectric order is noticed under atomic resolution images via scanning transmission electron microscopy. This work offers a breakthrough in synthesizing epitaxial PbSnO3 thin films and comprehensively understanding its anisotropic antiferroelectric behavior. Abstract : The epitaxial PbSnO3 (PSO) thin films with different orientations are stabilized by pulsed laser deposition. Through electrical measurement, the typical antiferroelectricity of PSO can be confirmed. In addition, the antiferroelectric order of PSO is unveiled by scanning transmission electron microscopy. This work offers an appealing approach in synthesizing PSO and deeply explores its characteristics.